DAMPAK MUKA AIR TANAH DAN AMELIORAN TERHADAP KELEMBAPAN TANAH, EMISI CO2 DAN PRODUKSI KELAPA SAWIT PADA TANAH GAMBUT - Winarna, Winarna; Yusuf, Muhammad Arif; Rahutomo, Suroso; Sutarta, Edy Sigit (Pusat Penelitian Kelapa Sawit, 2017)
A field study on peat soil to investigate impacts of soil water table depth and soil ameliorant (steel sludge) had been carried out on mature oil palm. Three treatments of soil water table management and four rates of steel sludge application were applied in this study. Treatments of soil water table management were WLM1, WLM-2, and WLM-3, where soil water table depth was maintained at 35-50 cm, 60-75 cm, and >75 cm below the soil surface, respectively. Treatments of steel sludge were application of this soil ameliorant at the rate of 0; 3.15; 6.51; 9.86 kg tree-1. The study was arranged as split plot randomized block design by assigning soil water table management as main plot and rate of steel sludge as sub plot. Soil Data observed were actual soil water content, peat soil properties, CO2 emission, vegetative growth, and palm yield. The results showed that maintaining soil water table depth at < 75 cm could maintain actual soil moisture up to top parts of peat soil. On the other hand, deeper soil water table (>75 cm, WLM-3) caused significant effects on decreasing of soil moisture in the 0-10 cm layer of peat soil. CO2 emission was 37, 40, dan 45 ton ha-1 year-1 under WLM-1, WLM-2, and WLM-3, respectively. The drop of soil water table to >75 cm (WLM-3) significantly increased CO2 emission to about 11-18% higher than that on WLM-1 and WLM-2. Steel sludge application did not significantly decrease CO2 emission. The highest FFB yield was observed under WLM-1, then followed by WLM-2 and WLM-3. FFB yield was significantly higher when soil water depth was maintained at 35-75 cm than that at > 75 cm, it was 7-10% and 36-60% higher in 2014 and 2015, respectively. There were no significant effects of steel sludge application on FFB yield, but there was improvement on average bunch weight.